Adapting to the new normal: practices in virtual teaching and research - Lee, Suzie Sukyoung; Erman, Didem; Chowdhury Turin, Tanvir (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2021)
Virtual engagement has become a new normal in the times of COVID-19 pandemic. As a group of students and researchers who work to empower youth in health advocacy by leading education programs and engaging in discussions with youth, it was also necessary for us to transition from classrooms to online meetings. The biggest challenge we faced in our implementation was creating an engaging learning environment and facilitating active discussions. This paper explores the different strategies and tools that we have used to meaningfully engage the youth participants for teaching and research.